Some New Challenges of Cybercrime and Reasons Why Regulations are Outdated - Anri Nishnianidze (European Scientific Journal, ESJ, 2022)
Purpose – The purpose of the research is to show what cybercrime is and how the arsenal of cybercriminals has evolved and legal regulations that exist today no longer respond to the challenges that would make the battle against cybercrime effective. Design/methodology/approach – The author of the research searched for the latest legal and multidisciplinary literature on the issue of cybercrime. Using various scientific methods, the mentioned literature was analyzed and summarized to present the essence and problems of fighting against cybercrime. Findings – In the conditions of modern technological development, there are many benefits along with negative facts. Cyberspace is not a safe place for the majority of the population. During the search process, it appeared that, with the arrival of each new day, the arsenal of cybercriminals is getting richer, to which the law enforcement structures do not have an appropriate response. Consequently, the process of battling cybercrime becomes difficult due to outdated legal regulations. Research limitations/implications – The research examined the latest opinions that are being debated in international legal circles. The problems that are on the agenda and which are important to solve have appeared. Accordingly, the paper offers the latest ways to correct the current situation, make recommendations and solve existing problems. Originality/value – Cyberspace is the most important space for many people, also for private and public structures. Solving the current issues on the agenda is important to make working in cyberspace safe for each person and organization.